Effect Of Pomegrante Peels And Bay Leaves On Multidrug Resistant Bacteria Isolated From Urinary Tract Infection Patients - Majeed, Huda Zuheir (AL-Kindy College Medical Journal, 2019)
Background: Alternative natural therapy by plants extracts had opened  wide  door   for   the    use  of  natural products as an alternative therapy instead of many antibiotics and drugs , which had many harmful side effects.Also, an increased interest has been centered on the industrial wastes, especially plant raw materials which contain phenols (e.g. Pomegranate peel and Bay leaves) which is a sources of natural antioxidants ,which are on the contrary  of  synthetic  antioxidants that  had restrict use  due to  their  health  risks , carcinogenesis and toxicity .Objectives :This study was done to find out the etiology and sensitivity pattern of uropathogenic bacteria isolated from patients with urinary tract infection , in order to select the bacterial isolates that had multidrug resistance .Type of the study: Cross-sectional study.Methods: preparation of   Hot water extract , Cold water extract , Methanol extract  and Ethanol extract of both Pomegranate peels and Bay leaves and test   there    antibacterial activity against these uropathogenic bacteria which are multidrug resistant .Results :All extracts from pomegranate fruit peels exhibited inhibitory activity against all tested bacteria . Hot , Cold  water extract and Ethanol extract of pomegranate peels recorded the highest inhibition zones compared with the Methanol extract. On the other hand, there were no antibacterial activity of any extract of  Bay leaves on any of tested bacteria. The  medicinal  plants antibacterial activity was well  documented  and  those  plants are new potential alternative antibacterial agent  especially  against multi resistant bacteria which had been the center of focus globally. Conclusions: Pomegranate have antibacterial activity  against multidrug resistant pathogenic bacteria isolated from UTI patients , So it emerged as alternative therapy for humans leading  to reduction the cost and the risk of using antibiotics .